Pharmacokinetics of the Cardioprotective Drug Dexrazoxane and Its Active Metabolite ADR-925 with Focus on Cardiomyocytes and the Heart - Jirkovský, Eduard; Jirkovská, Anna; Bureš, Jan; Chládek, Jaroslav; Lenčová, Olga; Stariat, Ján; Pokorná, Zuzana; Karabanovich, Galina; Roh, Jaroslav; Brázdová, Petra; Šimůnek, Tomáš; Kovaříková, Petra; et al. (The Journal of pharmacology and experimental therapeutics, 2018)
Dexrazoxane (DEX), the only cardioprotectant approved against anthracycline cardiotoxicity, has been traditionally deemed to be a prodrug of the iron-chelating metabolite ADR-925. However, pharmacokinetic profile of both agents, particularly with respect to the cells and tissues essential for its action (cardiomyocytes/myocardium), remains poorly understood. The aim of this study is to characterize the conversion and disposition of DEX to ADR-925 in vitro (primary cardiomyocytes) and in vivo (rabbits) under conditions where DEX is clearly cardioprotective against anthracycline cardiotoxicity. Our results show that DEX is hydrolyzed to ADR-925 in cell media independently of the presence of cardiomyocytes or their lysate. Furthermore, ADR-925 directly penetrates into the cells with contribution of active transport, and detectable concentrations occur earlier than after DEX incubation. In rabbits, ADR-925 was detected rapidly in plasma after DEX administration to form sustained concentrations thereafter. ADR-925 was not markedly retained in the myocardium, and its relative exposure was 5.7-fold lower than for DEX. Unlike liver tissue, myocardium homogenates did not accelerate the conversion of DEX to ADR-925 in vitro, suggesting that myocardial concentrations in vivo may originate from its distribution from the central compartment. The pharmacokinetic parameters for both DEX and ADR-925 were determined by both noncompartmental analyses and population pharmacokinetics (including joint parent-metabolite model). Importantly, all determined parameters were closer to human than to rodent data. The present results open venues for the direct assessment of the cardioprotective effects of ADR-925 in vitro and in vivo to establish whether DEX is a drug or prodrug.
Keywords: Rabbits; Ethylenediamines; Dexrazoxane; dexrazoxan; králíci; Glycine; zvířata; Myocytes, Cardiac; kardiomyocyty; ethylendiaminy; kardiotonika; Animals; Rats; glycin; tkáňová distribuce; Tissue Distribution; Cardiotonic Agents; krysa rodu Rattus